FRI0453 Damage Accrual in Patients with Eosinophilic Granulomatosis with Polyangiitis (EGPA): Analysis of 53 Patients. (10th June 2014) - Baldini, C.; Ferro, F.; Luciano, N.; Cacciatore, C.; L'abbate, S.; Di Colo, G.; Tavoni, A.; Mosca, M.; Talarico, R.; Bombardieri, S.
Abstract : Objectives: The Vasculitis Damage Index (VDI) is the accepted measure of permanent organ damage in eosinophilic granulomatosis with polyangiitis (EGPA). We analyzed data from a single center EGPA cohort in order to assess the type and extent of the damage accrued by the patients during the course of the disease and to examine the relationship between the VDI score and patients' characteristics, disease activity at baseline, and pre-existing chronic comorbidities. Methods: Unselected patients with a diagnosis of EGPA made according to the ACR 1990 criteria were included in this single center observational study. Patients' cumulative clinical and serological features were retrospectively retrieved. The VDI score was calculated at the last available follow up visit. Items of damage were analyzed by presumed etiology (i.e., secondary to EGPA, to therapy, or both) and time of occurrence. A VDI≥5 indicated severe damage. Disease activity at the time of diagnosis was assessed retrospectively using the Birmingham Vasculitis Activity Score (BVAS) and pre-existing comorbidities at the diagnosis were scored using the Charlson Comorbidity Index (CCI). Comparison in terms of continuous data were determined using independent sample t tests or Mann–Whitney tests, and in terms of proportions using contingency table analysis and Fisher's Exact test. Spearman's rank correlation coefficients were calculated between VDI scores and disease duration, age at the diagnosis, the BVAS at the baseline, frequency of flares, FFS, duration of glucocorticoid use and CCI. Results: The study included 53 EGPA patients (27 F: 26 M) with a median age at diagnosis of 52 (IQR 34.5-61) years and a median disease duration of 75 (IQR 31-154) months. At the end of the follow-up the median VDI score was 4 (IQR 2.5-5) and 17 patients out of 53 (32.1%) presented a severe damage. A priori defined treatment–related damage manifestations were described in 32/53 patients (60.4%) including: osteoporosis (45.3%), diabetes (5.7%), cataracts (19%), atrophy and weakness (9%), malignancy (5.7%), gonadal failure (5.7%), marrow failure (1.9%), chemical cystitis (1.9%), avascular necrosis (none). In addition, damage manifestations potentially associated to both treatment and disease activity included: hypertension (15%), angina/coronary artery disease (3.7%), alopecia (1.9%), cerebrovascular accident (1.9%), myocardial infarction (1.9%) and mouth ulcers (1.9%). The VDI score significantly correlated with the age of the patients at diagnosis (r=0.329; p=0.02), disease duration (r=0.437; p=0.001), number of flares (r.333=; p=0.015), and CCI at the baseline (r=0.384; p=0.01). Treatment-related damage manifestations were more frequent in older patients, in subjects with higher CCI at the baseline and in those with a longer length of glucocorticoid use. No significant correlation was detected between VDIand FFS, BVAS at the onset of the disease or ANCA status. Conclusions: Our findings indicate that the accrued damage in EGPA is not negligible. Age at the onset of the disease, pre-existing comorbidities, relapses and corticosteroid use appeared to be strongly correlated to damage accrual. These data clearly point out the need for individualized steroid-sparing treatments in EGPA. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4523